Is education level, as a proxy for socio-economic position, related to device-measured and self-reported sedentary behavior in European older adults? A cross-sectional study from the SITLESS project - Rodriguez Roca, Beatriz; Tully, Mark A.; Sansano-Nadal, Oriol; Caserotti, Paolo; Coll-Planas, Laura; Roqué, Marta; Brønd, Jan; Blackburn, Nicole E.; Wilson, Jason J.; Rothenbacher, Dietrich; McIntosh, Emma; Deidda, Manuela; et al. (Frontiers in Public Health, 2023)
We aimed to examine the associations between educational level and self-reported along with device-measured SB in older adults living in Europe and the association of mentally active and passive SB domains with the educational level and gender in these associations.The design is cross-sectional. SB was assessed with the Sedentary Behaviour Questionnaire and with an accelerometer. Multiple linear regression models were used to study the association between the level of education and SB. One-thousand threehundred and sixty participants aged 65 and over. Descriptive variables were assessed with an interview and device-measured was assessed with an accelerometer.Results: Participants self-reported an average of 7.82 (SD:3.02) daily waking hours of SB during weekend days. Education level was significantly associated with self-reported mean hours per day in SB (p=0.000; R=0.026; 95%CI).Conclusions: Low education level in older adults is associated with self-reported SB but not with objective SB measures.